PENGENALAN MANAJEMEN PEMELIHARAAN SAPI PERAH BERDASARKAN PEDOMAN GOOD DAIRY FARMING PRACTICE (GDFP) DI DESA WESALO, KABUPATEN KOLAKA TIMUR - Asminaya, Nur Santy; Auza, Fuji Astuty; Abadi, Musram; Asni, Nur; Agustina, Dian; Afyudi, Bobby; Tasse, Andi Murlina; Yaddi, Yamin; Fitrinaingsih, Fitrinaingsih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2024)
Dairy cows as milk-producing livestock will show their best performance if their maintenance management is carried out well. Good dairy cattle management can be done by referring to Good Dairy Farming Practice (GDFP). This service activity was carried out to increase the knowledge and skills of dairy farmers in Wesalo Village, Lalolae Village, East Kolaka Regency. The stages of this activity include: 1). activity preparation; 2. technical guidance on management of dairy cattle maintenance according to GDPP; 3. monitoring and evaluating activities. This activity is very beneficial for breeders in Wesalo Village because the breeders are new to and starting to raise dairy cattle. During the activity, the breeders were very active in discussing and enthusiastically listening to the speakers' presentations. Breeders are also very enthusiastic and focused on paying attention to the technical guidance provided during direct visits to the breeder's pen. Implementation of GDFP can be carried out by paying attention to aspects: 1). breeding and reproduction; 2). provision of feed and drinking water; 3). management; 4). cages and equipment; 5). livestock health and welfare. This community service activity closed with monitoring and evaluation to determine the level of understanding and help farmers who experience difficulties in raising dairy cattle. This activity can increase the knowledge and skills of farmers so they can maintain and develop dairy cows.